Application of the collaborative learning model to improve 21st-century civic skills - Suyato; Hidayah, Yayuk; Septiningrum, Lutfia; Arpannudin, Iqbal (Journal of Education and e-Learning Research, 2024)
The study examines the application of the collaborative learning model to improve 21st-century civic skills. The 21st century presents a number of unique challenges in the world of education. Rapid changes in technology, economics, and politics have placed new demands on individual learning and development. One of the key aspects of preparing students for these challenges is the development of strong civic skills. These skills include not only an understanding of the duties and rights of citizens but also the ability to collaborate with diverse individuals and groups in order to create positive change in society. The application of the Collaborative Learning Model has emerged as a highly relevant approach to developing civic skills in the modern era. This model emphasizes cooperation, active engagement, and knowledge sharing between students, which encourages them to collaborate in solving social problems, understanding cultural differences, and designing innovative solutions. In this study, the research method he research method in this study was a pseudo-experiment with a non-equivalent control group design. The data analysis technique used is the independent sample t-test with a significance level of 5%. Results showed that the model applied significantly influenced students’ 21st-century citizenship skills, and collaborative learning models effectively improved these skills. This study concludes that the Collaborative Learning Model can be used to improve students’ 21st-century civic skills.